Phosphorylation of the Proapoptotic BH3-Only Protein Bid Primes Mitochondria for Apoptosis during Mitotic Arrest - Wang, Pengbo (Cell Press, 2014)
Mitosis is a moment of exquisite vulnerability for a metazoan cell. Failure to complete mitosis accurately can lead to aneuploidy and cancer initiation. Therefore, if the exit from mitosis is delayed, normal cells are usually removed by apoptosis. However, how failure to complete mitosis activates apoptosis is still unclear. Here, we demonstrate that a phosphorylated form of the BH3-only protein Bid regulates apoptosis if mitotic exit is delayed. Bid is phosphorylated on serine 66 as cells enter mitosis, and this phosphorylation is lost during the metaphase-to-anaphase transition. Cells expressing a nonphosphorylatable version of Bid or a BH3-domain mutant were resistant to mitotic-arrest-induced apoptosis. Thus, we show that Bid phosphorylation primes cells to undergo mitochondrial apoptosis if mitotic exit is delayed. Avoidance of this mechanism may explain the selective pressure for cancer cells to undergo mitotic slippage.